2014
DOI: 10.4081/ijas.2014.3432
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stall Finishing of Podolian Young Bulls Raised on Pasture on Fatty Acid Composition and Oxidative Status of Meat

Abstract: Sixteen Podolian young bulls were used to study the effects of two different feeding systems on fatty acids composition and oxidative stability of meat: C group, eight young bulls were kept indoors and fed with commercial concentrate for all experimental period (260 days); PC group, eight young bulls were allowed to graze a pasture for 200 days and shifted indoor, fed with concentrate, 60 days before being slaughtered. Meat from young bulls that were allowed, before stall finishing with concentrate, to graze a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Similarly, in our study, the higher C18:3n-3 and lower C18:2n-6 concentrations for the GSPC bulls compared to GSC and C bulls are indicative of inclusion of grazed grass in the diet of the bulls. This shows that finishing on concentrate diets, up to 71 days in our case, may not entirely eliminate the contribution to muscle fatty acids of grazed grass offered prior to the finishing period, which was in agreement with Scerra et al (2014) in a study conducted over a relatively shorter finishing period (60 days).…”
Section: Fatty Acid Compositionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, in our study, the higher C18:3n-3 and lower C18:2n-6 concentrations for the GSPC bulls compared to GSC and C bulls are indicative of inclusion of grazed grass in the diet of the bulls. This shows that finishing on concentrate diets, up to 71 days in our case, may not entirely eliminate the contribution to muscle fatty acids of grazed grass offered prior to the finishing period, which was in agreement with Scerra et al (2014) in a study conducted over a relatively shorter finishing period (60 days).…”
Section: Fatty Acid Compositionsupporting
confidence: 91%
“…In the present study, its concentration was similar among all treatments. As shown by Scerra et al (2014), a higher C18:2c9,t11 content was reported from LT muscle of bulls fed on pasture prior to finishing on concentrate diet compared to bulls raised on concentrate diet only. However, compared to our study, the pasture feeding period was longer (200 vs 100 days) and the concentrate finishing period was shorter (60 vs 71 days) in the study of Scerra et al (2014) which may have contributed to a greater effect of the pasture diet on this particular isomer.…”
Section: Fatty Acid Compositionmentioning
confidence: 77%
See 2 more Smart Citations
“…The rocky Mountains here are classified as low mountains. The rocky Mountains of Syugata are a mountain range consisting of strongly cut, rocky slopes consisting of open rocky rocks and high cliffs forming a gorge [12].…”
Section: Research Results and Their Analysis Ecological Conditions Ofmentioning
confidence: 99%